Parental awareness and knowledge of first aid for children in Saudi Arabia: a multiregional cross-sectional study - Alotaibi, Ola; Alrayya, Sarah; Alotaibi, Shahad; Algoraini, Yara (Frontiers in Pediatrics, 2025)
BackgroundFirst aid (FA) knowledge is crucial for parents to effectively respond to pediatric emergencies, and it can potentially save lives and reduce injury severity. Despite the high rates of childhood accidents such as burns, choking, and drowning, limited data exist on parental awareness of FA in Saudi Arabia across various situations. The aim of this study was to assess parental knowledge and awareness regarding FA for children in Saudi Arabia.MethodsThis cross-sectional study using a self-administered electronic questionnaire was conducted via social networking sites between March and April 2024. The questionnaire was developed from a literature review and validated by experts. A total of 1,421 parents aged ≥18 years and residing in Saudi Arabia participated. Data were analyzed using descriptive statistics and logistic regression analysis.ResultsThe participants were predominantly women (59.3%), Saudi nationals (85.1%), married (90.6%), and university graduates (68.3%). While 73.6% believed they had good FA knowledge, only 25.6% had attended a formal FA course. With regard to knowledge gaps, 44.12% parents incorrectly believed that they should encourage a choking child aged <1 year to cough, while 61.44% incorrectly believed that ice should be applied to burns; only 51.02% parents knew that cool water should be run over burns. Logistic regression analysis showed that non-Saudi nationality and previous FA experience were significant predictors of willingness to attend FA courses (p = 0.045 and p = 0.012, respectively). Barriers to FA knowledge included underestimation of the problem (39.3%) and lack of information from healthcare personnel (28.1%). Preferred methods for gaining FA knowledge were inclusion of FA in educational curricula (59.7%) and programs in primary healthcare centers (19.5%).ConclusionThere are significant gaps in parental knowledge regarding FA for children in Saudi Arabia. These gaps need to be addressed through structured educational programs and accessible resources in order to enhance preparedness for pediatric emergencies among parents. Recommendations include implementation of FA training programs, integration of FA into school curricula, development of educational materials in Arabic, and promotion of mandatory FA training during prenatal and postnatal care visits.